Heart rate variability and its correlation with pulmonary function test of smokers - Joshil Kumar Behera; Sushma Sood; Naresh Kumar; Kirti Sharma; Reshmi Mishra; Prasanta Saha Roy (Heart Views, 2013)
Context: Though many studies have been conducted on the effect of chronic smoking on pulmonary function test (PFT) and heart rate variability (HRV), no study has found a correlation between the pulmonary function test and heart rate variability parameters so far. Aim: The aim was to study if there was a correlation, if any, between PFT and HRV. Settings and Design: Thirty male subjects who were chronic smokers of at least 10 pack years and another 30 nonsmoking healthy males were included in the study and were matched for age, height, weight, and body surface area. Materials and Methods: PFT and HRV were performed on these subjects and a correlation was statistically derived. Statistical Analysis Used: Spearman′s correlation coefficient was used for the analysis of HRV and PFT. Multiple stepwise regression analysis was used subsequently. Results: HF and LF showed correlation coefficients of 0.378 and-0.383 with forced expiratory volume in the first second (FEV 1 ) and peak expiratory flow rate (PEFR), respectively. It was found that only FEV 1 /FVC was having a statistically significant regression coefficient with HF the R-value was found to be 0.425 while with other parameters, it was not significant. Conclusion: We conclude that smoking affects all the parameters of PFT and HRV. Since there is a correlation between PFT parameters (PEFR and FEV 1 ) and HRV parameter (LF and HF), this can help us in predicting cardiac morbidity in chronic smokers. So HRV should be included as a routine test along with PFT in chronic smokers for early diagnosis of cardiac involvement.